Identification of Cryptosporodium from Dairy Cattle in Pahang, Malaysia - Hisamudin, Nur Hazirah; Hashim, Najat; Mohd Amin, Mohd Hishammfariz; Abdul Wahab, Ridhwan; Mohammad, Mardhiah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Korean Society for Parasitology and Tropical Medicine, 2016)
Cryptosporidium, a protozoan parasite, can cause cryptosporidiosis which is a gastrointestinal disease that can infect humans and livestock. Cattle are the most common livestock that can be infected with this protozoan. This study was carried out to determine the prevalence of Cryptosporidium infection in cattle in Kuantan, Pahang, Malaysia and to find out the association between the occurrence of infection and 3 different ages of cattle (calves less than 1 year, yearling, and adult cattle). The samples were processed by using formol-ether concentration technique and stained by modified Ziehl Neelsen. The results showed that 15.9% (24/151) of cattle were positive for Cryptosporidium oocysts. The occurrence of Cryptosporidium in calves less than 1 year was the highest with the percentage of 20.0% (11/55) followed by yearling and adult cattle, with the percentage occurrence of 15.6 % (7/45) and 11.8% (6/51), respectively. There was no significant association between the occurrence and age of cattle and presence of diarrhea. Good management practices and proper hygiene management must be taken in order to reduce the infection. It is highly important to control the infection since infected cattle may serve as potential reservoirs of the infection to other animals and humans, especially animal handlers.